Peran Posyandu Lansia dalam Pemenuhan Kebutuhan Sosial Lansia di Desa Babul Makmur Kabupaten Simeulue - Iis Maryuni; Rahma Husna Yana (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The elderly are a group of people who go through a gradual process of change over a certain period of time. The changes that occur include changes in the physical, biological, cognitive, psychological, economic and social roles in society. These changes often cause problems in the lives of older adults. The elderly need to receive guidance to improve their quality and productivity to achieve an adequate life, one of which is through posyandu services for the elderly. This study aims to describe the status of old age insurance, the role of old age insurance in improving the welfare of the elderly, and the factors that influence the implementation of old age insurance. This study uses a qualitative approach. The research location was taken in Babul Makmur Village, West Simeulue District, and then the researchers conducted interviews with informants, namely 1 village midwife, 2 Kade people, 4 village people, so that the total informants were 1,500 people. Data were collected by interview, observation, and documentation. The results of the research are the role of the Elderly Posyandu in Fulfilling the Social Needs of the Elderly in Babul Makmur Village, Simeulue Regency. Services provided, such as blood pressure and weight checks. Elderly Posyandu activities help fulfill basic needs such as physiology, security, socialization, wanting to be appreciated and self-actualization. In addition, older adults can cope with their problems and still interact with their family, peers, and community. Suggestions for the prosperous elderly posyandu is to resume activities that had been stopped so that the elderly can feel the benefits more.